Chenin blanc Wine Volatiles and the Intensity of a Guava-like Flavour - van Rooyen, P. C.; de Wet, P.; van Wyk, C. J.; Tromp, A. (South African Journal of Enology and Viticulture, 2017)
A guava-like flavour occurring in some South African Chenin blanc and Colombard dry white wines was investigated. Headspace volatiles of some of these wines, as well as those of fresh guava fruits, were analysed by means of a gas chromatograph equipped with a "sniffer-detector". In contrast to the headspace concentrate of guava fruits, no single fraction with a typical guava flavour was found in the wines analysed. The pattern recognition system "ARTHUR" was therefore used to investigate relationships between the more important wine volatiles and the intensity of a guava-like flavour of a set of wines originating from the same Chenin blanc must. Sensory scores for this flavour were used in both category and continuous property analysis in each case. Category and correlation to property plots were used to elucidate the results. Several promising variables and ratios between variables were singled out for further investigation, notably ethyl butyrate and the ratios ethyl butyrate/ethyl decanoate and ethyl butyrate/ethyl octanoate.